Application of Earth Observation Technology to Site Selection and Development of Ecotourism Management Plans in Rural Ghana. (3rd January 2013) - Adanu, Selase Kofi; Mensah, Foster Kwami; Adanu, Sesime Kofi; Adanu, Dziwornu Kwami; Abass, Kabila
Abstract : Production of development plans is vital for sustainable ecotourism development given the increasing competition for land to satisfy various human needs including agriculture, timber, and wood energy. Such human activities cause rapid destruction of wildlife habitat and loss of indigenous tree species. To enhance sustainable use of the flora and fauna to promote rural tourism in Ghana, seven eco-tourism sites have been surveyed to produce data for management plans to be developed for these sites. The survey focused on the status of flora and fauna at the sites, infrastructure, cultural dynamics, cross-border issues, and revenue mobilization. Key findings indicate lack of infrastructure at the sites and substantial loss of forest cover over seventeen years covered by the survey.